Preceptorship as part of the recruitment and retention strategy for nurses? A qualitative interview study. (4th May 2021) - Jönsson, Sandra; Stavreski, Helena; Muhonen, Tuija
Abstract: Aim: To explore aspects that are important for the integration of preceptorship and processes for recruitment and retention of nurses. Background: The shortage of nurses is a global concern that has a major impact on health care systems around the world. However, earlier research has not considered whether preceptorship of nursing students can be an integral part of recruitment and retention of nurses. Method: A descriptive design with a qualitative approach was used. Semi‐structured interviews were conducted with ten preceptors and six ward managers in different health care specialties in Sweden. Results: Three aspects were found central for integrating preceptorship with recruitment and retention: perceptions of preceptorship, the organisation of preceptorship and the way preceptorship operates in relation to recruitment and retention strategies. Conclusion: The findings suggest that preceptorship and recruitment strategies could both benefit from being integrated. Implications for Nursing Management: It is central for nursing managers to develop organisational practices that enable the integration of preceptorship with recruitment and retention of nurses. This could increase the quality of both preceptorship and the work environment in general.